Combining computational linguistics with sentence embedding to create a zero-shot NLIDB - Perezhohin, Yuriy (2024)
Perezhohin, Y., Peres, F., & Castelli, M. (2024). Combining computational linguistics with sentence embedding to create a zero-shot NLIDB. Array, 24, 1-11. Article 100368. https://doi.org/10.1016/j.array.2024.100368 --- This work was supported by MyNorth AI Research. This work was partially supported by national funds through the FCT (Fundação para a Ciência e a Tecnologia) by the project UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.